2021
DOI: 10.1371/journal.ppat.1009412
|View full text |Cite
|
Sign up to set email alerts
|

The proximal proteome of 17 SARS-CoV-2 proteins links to disrupted antiviral signaling and host translation

Abstract: Viral proteins localize within subcellular compartments to subvert host machinery and promote pathogenesis. To study SARS-CoV-2 biology, we generated an atlas of 2422 human proteins vicinal to 17 SARS-CoV-2 viral proteins using proximity proteomics. This identified viral proteins at specific intracellular locations, such as association of accessary proteins with intracellular membranes, and projected SARS-CoV-2 impacts on innate immune signaling, ER-Golgi transport, and protein translation. It identified viral… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 104 publications
3
20
2
Order By: Relevance
“…Given that the protease mutant nsp5 of SARS-CoV-2 could not repress p53-mediated promoter activation ( Figure 2 ), it is possible that nsp5 can also directly degrade either p53 or a co-factor of p53 that is required for the transcriptional activity of p53. Although we did not detect p53 protein degradation by nsp5, a recent study found that p53 protein expression can be downregulated by nsp5 to some degree [ 33 ]. Interestingly, most of the host proteins whose abundance is decreased by nsp5 did not interact with nsp5, indicating that depletion of host proteins by nsp5 may be an indirect effect of nsp5 activity [ 33 ].…”
Section: Resultscontrasting
confidence: 86%
See 1 more Smart Citation
“…Given that the protease mutant nsp5 of SARS-CoV-2 could not repress p53-mediated promoter activation ( Figure 2 ), it is possible that nsp5 can also directly degrade either p53 or a co-factor of p53 that is required for the transcriptional activity of p53. Although we did not detect p53 protein degradation by nsp5, a recent study found that p53 protein expression can be downregulated by nsp5 to some degree [ 33 ]. Interestingly, most of the host proteins whose abundance is decreased by nsp5 did not interact with nsp5, indicating that depletion of host proteins by nsp5 may be an indirect effect of nsp5 activity [ 33 ].…”
Section: Resultscontrasting
confidence: 86%
“…Although we did not detect p53 protein degradation by nsp5, a recent study found that p53 protein expression can be downregulated by nsp5 to some degree [ 33 ]. Interestingly, most of the host proteins whose abundance is decreased by nsp5 did not interact with nsp5, indicating that depletion of host proteins by nsp5 may be an indirect effect of nsp5 activity [ 33 ]. In fact, p53 has not yet been detected in any nsp5 interactomes so far.…”
Section: Resultscontrasting
confidence: 86%
“…Previous attempts to map the SARS-CoV-2 viral interactome have varied in experimental approach, data analysis parameters, cell lines used, and specific viral baits [ 11 , 12 , 13 , 14 , 15 , 16 , 18 , 19 , 20 , 21 ]. Unlike previous BioID reports, we report here both global proteome analysis and BioID-based proximity interactome analysis in human A549 lung cells for all but three SARS-CoV-2 viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…A crucial component of the effort to study COVID-19 is the application of technologies that reveal how viral proteins behave in host cells. Current efforts to map the SARS-CoV-2 virus-host interactome have offered great insight into possible pathways directly affected by various viral proteins, yet differences in experimental approaches and data analysis methods inevitably lead to discrepancies when comparing reported interactomes [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. As with any large-scale approach to identifying gene or protein networks, false positives due to background contamination can hinder accurate data interpretation; therefore, the use of several approaches with multiple replicates by multiple independent studies will be required to ultimately map the full SARS-CoV-2 interactome.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of NSP1 can also compete with mRNA for binding to the 40S subunit and prevent proper accommodation of mRNA ( 107 ). In a recent study, NSP1 was found near the position of the eIF3 translation initiation complex and inhibited protein translation ( 116 ). After translation termination, NSP1 can bind to 80S ribosomal complex, suggesting that NSP1 may be involved in translation termination, which has been confirmed by a recent study ( 117 ).…”
Section: Sars-cov-2 Suppresses Host Protein Translationmentioning
confidence: 99%